Biotechnology - Kück, H.-U., 1950-; Frankenberg-Dinkel, Nicole (Walter de Gruyter GmgH & Co. KG, 2015)
This textbook presents processes, modern research and applications in white, red, green and blue biotechnology using a color-coded classification. General introductions, concluding paragraphs, key terms, addressed problems, and recommended additional readings to each chapter are ideally suited for advanced graduate or master students and will also be a good reference for PhD students, physicians, engineers, attorneys.
Keywords: Biotechnology.; Bioengineering.; elektronické knihy; electronic books